Formação de docentes em nível médio – modalidade normal: o curso que resiste e persiste no estado do Paraná - Gabre, Viviane (2022)
The research analyzes the High School Teacher Training, Normal type, of Paraná’s public education system (2004-2020). It is linked to the line of research Culture, Educational Processes, and Teacher Training, of the Master’s Program in Education, in the city of Francisco Beltrão (PPGEFB), at Western Paraná State University (UNIOESTE). Since the promulgation of LDBEN, num. 9.394/1996, teacher training locus is marked by ambiguities and contradictions, both at federal and state levels. From 1996 on, the State of Paraná, in advance to LDBEN num. 9.394/1996 and the Federal Decree num. 2.208/1997, which separated high school from Vocational Education, to implement the Programa Expansão, Melhoria e Inovação do Ensino Médio (PROEM), the Paraná government stopped vocational courses, such as the teaching course named Curso de Magistério. The resistance and persistence of 14 state public teaching institutions, that did not accept PROEM and kept offering students their teaching courses, and the revocation of the Decree num. 2.208/1997, provided the resumption of Vocational Education attached to Paraná’s public high schools. In this context, our research problem is: To what extent did the conflicts and contradictions that marked the history of the Normal high school course lead to their resumption, in 2004, in the State of Paraná? Bearing this in mind, our general objective is to analyze the socio-historical trajectory of the high school Teacher Training Course (Curso de Formação de Docentes), Normal type, in Paraná from its resumption at state public institutions in 2004. We used the bibliographic and document method, using opinions, resolutions, laws, the course’s Pedagogical Curriculum Proposal, the political and pedagogical grounds of Vocational Education of Paraná State, and the National Education Plan. We also surveyed statistical data available at the National Institute for Educational Studies and Research (INEP) and Dia a Dia Educação portal. Our study is grounded on a critical-dialectical approach, using a theoretical framework that enabled us to analyze our research object establishing a relationship between education and society. Authors such as Romanelli (2002), Saviani (2004, 2006, 2009), Ribeiro (2011) have contributed for us to understand the historical trajectory of Normal course. Frigotto, Ciavatta and Ramos (2005) were also used to clarify issues related to Vocational Education’s restructuration. When analyzing our data, we concluded that the repeal of the Decree no. 2.208/1997, replaced by Decree no. 5.154/2004, which deal with vocational education, and the change in public administration in the federal and state levels, have led to resumption of the Normal high school course. However, decrease in the number of enrollments from 2006 to 2020 in the state of Paraná. In this contradictory movement, sometimes in favor of its own permanence, sometimes in favor of its exclusion of the public system of Paraná, the Normal high school course continues to be a training opportunity for working class students. Somehow, it also contributes to amplify the number of hours of the training process, as many of them, when they start teaching, keep on studying at a continued education level. Our findings point to contradictions, because young people, in their search for immediate high school technical education, postpone their higher education training, as this one is only available after they start working as teachers and, above all, distance courses, which implies the precariousness and flexibilization of teacher training.